Chemical characterization of eleven Latin America woods (Research, Society and Development, 2025)
The forests of Latin America are home to diverse species of interest regarding the chemical constituents of wood. This calls for a comprehensive study of all wood characteristics, including their chemical characteristics. This article aimed to characterize the essential chemicals of 11 Latin American native forest species. From wood samples of trees more than 20 years of age, we determined the contents of total extractives, total lignin, holocellulose, and ash, as well as higher heating value. The usual standards were applied in each analysis. Analysis of variance and the Bonferroni test were used to determine differences among variables in each species. In all characteristics, the results varied among the different species. When compared with the results of other studies, we found that the differences in wood chemistry could be explained by differences in collection sites, soil composition or tree age. The main contribution and novelty of this study lies in disseminating to a wide number of professionals the variations found in the chemical constituents of the wood studied. Therefore, it is anticipated that the data revealed in this study will be of interest to scientific researchers and timber specialists alike.